Quality Of Child Health Services And Its Utilization Among Staff And Mothers In Selected Primary Healthcare Facilities In Enugu South Local Government Area Enugu State Nigeria - Okezue, Blessing; Ihudiebube-Splendor, Chikaodili Ndidiamaka; Judith Ilo, Ijeoma; Egbichi Israel, Chidinma (International Journal of Nursing and Health Services (IJNHS), 2026)
Background: Children carry a disproportionate burden of disease globally, and strengthening child health services (CHS) in primary health care (PHC) can improve access to safe, effective, quality, and affordable care. Objective: This study assessed the quality and utilization of CHS in two selected PHC facilities in Enugu South LGA, focusing on infrastructure, equipment and personnel; clinical consultation, diagnosis and treatment of common childhood illnesses; service utilization; and clients’ satisfaction. Method: A cross-sectional descriptive survey design was used, with researcher-developed questionnaires, and data were analyzed using SPSS version 25. Result: Findings showed that staffing was inadequate, with most providers being SCHEWs (35.2%) and JCHEWs (29.4%). Facility structures were largely adequate, but one PHC lacked a functional pharmacy and laboratory. Essential drugs and some key equipment were insufficient, although consultation processes and the diagnosis and treatment of common childhood illnesses were rated adequate. Overall service quality was reported as good across the two facilities (80% and 60%). Mothers had a mean age of 31.11 ± 6.09 years; over half had secondary education (52.7%), many were traders (36.0%), and most had 1–2 children (43.3%). Utilization of CHS was high (87.2% and 84.4%), and satisfaction levels were very high (97.9% and 99.4%). Conclusion: The study concludes that while utilization and satisfaction were high and clinical care was generally adequate, gaps remain in staffing and the availability of essential drugs and equipment, including pharmacy and laboratory services in one facility. Recommendation: It recommends improving staffing and training, providing basic amenities, and adopting standard minimum equipment and supply requirements for PHC facilities.